(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
Since the outbreak of the Israeli-Palestinian conflict there have been sporadic protests on American campuses calling for a ceasefire and supporting Palestine. The recent protest at Columbia University sparked a wave of similar actions across the nation. On April 17, a pro-Palestinian protest erupted at Columbia University, where students set up tents on campus to call for the university to divest from companies linked to Israel. The Columbia Daily Spectator, the student-run newspaper of Columbia University, stands as a prominent voice within the campus community, providing coverage and commentary on a wide range of social and political issues. This paper investigates the coverage of pro-Palestinian protests at Columbia University by The Columbia Daily Spectator from April 17 to May 17, 2024. The paper analyzes 143 reports, focusing on the language, narratives, and perspectives presented to understand how the campus media narrates the protest movement and shapes public discourse. Employing narrative analysis method, the findings reveal that the newspaper primarily adopts a chronological reporting style, vividly depicting the students commitment and urgency. Various voices are included, offering a balanced perspective on the motivations of all parties involved. However, the coverage reflects an implicit bias, often portraying the students as instigators of conflict while portraying the universitys responses- often involving suppression and police intervention- as necessary measures for safety concerns. The protests embody an anti-establishment sentiment, challenging prevailing political taboos, particularly regarding the US-Israel relationship. Notably, the absence of middle-ground voices in the coverage may lead to a one-sided interpretation of events, emphasizing the voices of influential groups while sidelining neutral or alternative viewpoints. In general, it becomes clear that the student newspaper constructs a story of committed and principled student activists standing up against a rigid and controlling administration.